Canine substitution of a missing maxillary lateral incisor in an orthodontic re-treatment case: long term follow up - Lupini, Daniela; Lempert, Susan M; Cozzani, Mauro (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: This case report describes the orthodontic re-treatment of a case with a severely compromised maxillary lateralincisor requiring removal and canine substitution. The treatment included creative asymmetric treatment mechanics and a careful management of anchorage.Case Presentation: Pre-treatment, post treatment and 5 years follow-up records are shown. The treatment outcomes proved to bestable at the follow-up with acceptable aesthetic and functional results.Conclusion: Through careful management of anchorage it was possible to successfully use asymmetric treatment mechanics to achievea good functional occlusion.